"Rustici" y bagaudas en Vasconia: la elección de un vocablo en Hidacio - Pozo Flores, Mikel (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2018)
This work looks at the classical subject of 5th Century Historiography, the famous Bagaudae Conflict mentioned in Hydatius’ Chronicle. Having briefly introduced the events and historiographical explanations, we will analyze the texts by looking at the features of intellectual production in the Late Antiquity. To be precise, we will study the meaning of the term bagaudae in work by other authors prior to Hydatius, in particular Orosius, and the parallelisms in the accounts of these authors. On the one hand we look to confirm the existence of a certain consolidated tradition amongst the intellectuals of the Antiquity in the meaning and usage of the term and on the other hand, hold that Hydatius did not refer to bagaudae as rebel peasants, as was hitherto maintained, but as a certain type of local troop known as rustici. This interpretation is in line with the decisive role that the rustici had in the evolution of Post-Roman Vasconia according to an in depth explanation being prepared for publication.